Learning through play: design and creation of a narrative Game-Based Learning experience - Vieira, Bruno Rodrigues; Santos, Caroline Queiroz (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Digital didactic games are promising tools to aid the teaching-learning process, as they bring the previously abstract content closer to the student’s reality. This study aimed to develop a narrative digital game to support the development of skills and knowledge of specific topics in engineering students. For this, it was necessary to study and understand the design and development process of an educational digital game, evaluating the playful and pedagogical elements that could be used. The work methodology was structured in three stages: 1) game design, 2) application of the game to the research participants, and; 3) data collection and analysis. The main perceptions of the participants about the game, the obstacles and facilitators during the gameplay, and the possible contributions in relation to the design and development of the game were analyzed. The results showed that game-based learning is promising and innovative, as it encourages students’ interest and motivation about the themes through resources beyond the classroom space.